1998
DOI: 10.1080/00224549809600384
|View full text |Cite
|
Sign up to set email alerts
|

Police Officers' Perceptions of Eyewitness Performance in Forensic Investigations

Abstract: Few contemporary data support the assertion that eyewitnesses are important in police investigations. In the present study, 159 UK police officers were surveyed regarding their perceptions of eyewitnesses and eyewitness performance. The respondents indicated that eyewitnesses usually provide the central leads in criminal investigations; however, the police officers also believed that eyewitnesses rarely provide sufficient information, especially descriptive details as opposed to action details. Nevertheless, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
109
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(112 citation statements)
references
References 12 publications
3
109
0
Order By: Relevance
“…Indeed, a majority of police officers agree that witness statements often provide major leads for an investigation (Coupe & Griffiths, 1996;Kebbell & Milne, 1998). However, memory is fallible, and eyewitnesses are often unable to recall sufficient details regarding important forensic details such as person descriptors (Kebbell & Milne, 1998).…”
Section: Self-administered Interviewmentioning
confidence: 99%
“…Indeed, a majority of police officers agree that witness statements often provide major leads for an investigation (Coupe & Griffiths, 1996;Kebbell & Milne, 1998). However, memory is fallible, and eyewitnesses are often unable to recall sufficient details regarding important forensic details such as person descriptors (Kebbell & Milne, 1998).…”
Section: Self-administered Interviewmentioning
confidence: 99%
“…The cognitive interview for witnesses with autism spectrum disorder Eyewitness evidence is central to the criminal justice system. In 2007, 1.78 million UK offenders were found guilty or cautioned (UK Ministry of Justice, UK, 2008) and 87% of police officers indicated that eyewitnesses usually or always provided major investigative leads (Kebbell & Milne, 1998). Inaccurate or incomplete testimony can lead to wrongful conviction or acquittal (Huff, Rattner, & Sagarin, 1996) and so reliable interviewing techniques are imperative in eliciting the most detailed yet accurate reports from witnesses.…”
mentioning
confidence: 99%
“…Evidence from eyewitnesses, and its reliability, is often a key element in judicial processes (Kebbell & Milne, 1998;Wells, Memon, & Penrod, 2006). Historically, child witnesses were thought to be inherently unreliable (Odegard & Toglia, 2013), but the consensus now is that even developmentally young children provide at least some accurate information if interviewed appropriately (Bull, 2010;.…”
Section: Introductionmentioning
confidence: 99%